Jawabanmu

Jawaban paling cerdas!
2014-04-20T13:48:59+07:00
1. cos x/ 1-tan x + sin x/1-cotan x = sin x + cos x
   cosx/(1-tanx)
  
= cos x/((cosx/cosx) -(sinx/cosx)) + sinx((sinx/sinx) - (cosx/sinx))
   = cosx/((cosx - snx)/cosx  + sinx/((sinx - cosx)/sinx)
   = cos²x/(cosx - sinx) + sin²x/(sinx - cosx)
   =
cos²x/(cosx - sinx) - sin²x/(cosx - sinx)
   = (cos²x - sin²x)/(cosx - sinx) atau
   = Cos2x/(Cosx - Sinx) ²berarti tidak terbukti

2.tan² x - sin² x = tan² x sin² x

   tan²x - sin²x = sin²x/cos²x - sin²xcos²x/cos²x
                     = (sin²x - sin²xcos²x)/cos²x
                     = sin²x(1 - cos²x)/cos²x
                     = sin²x(sin²x/cos²x)
                     = sin²xtan²x (komutatif) berarti terbukti


1 5 1